Medical devices: product safety and product liability issues - Amin, Naemah (2015)

(untitled)
The paper aims to provide an overview of the potential liability of a manufacturer or distributor or other persons in the chain of product distribution for supplying unsafe or substandard medical devices and for any damage caused by a defect in the device. Just like other products, medical devices are also subject to the law of product safety and product liability. The discussion on product safety focuses on the requirements of medical device safety under the Medical Device Act 2012 and criminal liability of the manufacturer, importer and distributor including the hospitals and doctors for non-compliance with the law. They may also subject to civil claims by patients under various product liability laws – contract, negligence and Part V and Part X of the Consumer Protection Act 1999. It is thus important for medical practitioners to have a clear understanding of these laws to avoid contravention and legal proceedings.